A comparative study on dynamic mechanical performance of concrete and rock (Fracture and Structural Integrity, 2015)
Recently, engineering blasting is widely applied in projects such as rock mineral mining, construction of underground cavities and field-leveling excavation. Dynamic mechanical performance of rocks has been gradually attached importance both in China and abroad. Concrete and rock are two kinds of the most frequently used engineering materials and also frequently used as experimental objects currently. To compare dynamic mechanical performance of these two materials, this study performed dynamic compression test with five different strain rates on concrete and rock using Split Hopkinson Pressure Bar (SHPB) to obtain basic dynamic mechanical parameters of them and then summarized the relationship of dynamic compressive strength, peak strain and strain rate of two materials. Moreover, specific energy absorption is introduced to confirm dynamic damage mechanisms of concrete and rock materials. This work can not only help to improve working efficiency to the largest extent but also ensure the smooth development of engineering, providing rich theoretical guidance for development of related engineering in the future.
Keywords: Dynamic mechanical performance